2020
DOI: 10.3390/ijms21124425
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Adenine Nucleotides and Adenosine Modulate the Growth and Survival of THP-1 Leukemia Cells

Abstract: A new approach to improve the effectiveness of acute myeloid leukemia (AML) treatment is to use the properties of purinergic signaling molecules secreted into the bone marrow milieu in response to leukemic cell growth. Therefore, our study aimed to evaluate the effects of extracellular adenine nucleotides and adenosine on the growth and death parameters in the leukemic THP-1 cell line. Cells were exposed to ATP, ADP, AMP, adenosine and nonhydrolyzable analogues of ATP and ADP (ATPγS and ADPβS) in a 1–1000 μM b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Our findings are in line with those of previous studies. In addition, our results further support the idea that NTs reduce DNA damage [ 24 , 25 ] and cell apoptosis [ 26 , 27 ], and promote cell proliferation [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…Our findings are in line with those of previous studies. In addition, our results further support the idea that NTs reduce DNA damage [ 24 , 25 ] and cell apoptosis [ 26 , 27 ], and promote cell proliferation [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to solid tumors, purinergic signaling in hematological malignancies has shown both tumor‐suppressing and tumor‐promoting effects. When THP‐1, a human leukemia monocytic cell line, is treated with adenosine derivatives, there is a decrease in leukemia cell growth and survival 137 . Conversely, the ATP/P2 × 7 axis increases acute myeloid leukemia (AML) leukemia burden which could be therapeutically targeted using a P2 × 7 receptor antagonist to reduce AML growth in mice 138 , 139 .…”
Section: Purinergic Signaling and Cancermentioning
confidence: 99%
“…When THP-1, a human leukemia monocytic cell line, is treated with adenosine derivatives, there is a decrease in leukemia cell growth and survival. 137 Conversely, the ATP/P2 × 7 axis increases acute myeloid leukemia (AML) leukemia burden which could be therapeutically targeted using a P2 × 7 receptor antagonist to reduce AML growth in mice. 138,139 What is clear from published studies is that purinergic signaling impacts the development of blood cancers; however, we are just beginning to scratch the surface in our understanding of this relationship.…”
Section: Purinergic Signaling and Tumor Developmentmentioning
confidence: 99%
“…We adopted THP-1 cell line as a model to assess how the adenosine deaminase encoded by THV_ADA and THV_ADA-SP elicits immunomodulatory activity on an immune cell population. It has been previously demonstrated that extracellular adenosine (eADO) inhibits THP-1 proliferation [62] by signaling through ADO receptors. As previously reported, THP-1 cells showed a medium-to-high expression rate of ADO receptors (Figure 5a) [62].…”
Section: Thv_ada and Thv_ada-sp Revert The Inhibitory Effect Of Adeno...mentioning
confidence: 99%
“…It has been previously demonstrated that extracellular adenosine (eADO) inhibits THP-1 proliferation [62] by signaling through ADO receptors. As previously reported, THP-1 cells showed a medium-to-high expression rate of ADO receptors (Figure 5a) [62]. We thus cultured THP-1 cells in media supplemented with increasing concentrations of adenosine (10 µM, 50 µM, 100 µM, 1000 µM, 2000 µM).…”
Section: Thv_ada and Thv_ada-sp Revert The Inhibitory Effect Of Adeno...mentioning
confidence: 99%